2013
DOI: 10.1177/0022002713498705
|View full text |Cite
|
Sign up to set email alerts
|

Hawks, Doves, and International Cooperation

Abstract: How does the hawkish or dovish nature of the domestic opposition in one state influence its own, as well as an international opponent's, negotiating behavior? I show that doves, when negotiating in the presence of a hawkish opposition, have more bargaining leverage in international negotiations. The key is to understand an international opponent's preference to deal with a dove rather than a hawk in future negotiations. I argue that adversaries have an incentive to concede more in negotiations to doves in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Studies such as Sigelman and Sigelman (), Cuckierman and Tommasi (), and Cowen and Sutter () assume that the “election” or “poll” happens before the response by the other state is known and thus before the policy can be deemed successful or not. More recent work (e.g., Clare ; Colaresi ; Davies and Johns ; Schultz ) takes into consideration that voters might update their opinions based on the adversary's reaction. Interestingly, these studies formulate quite different expectations about how voters respond to success and failure of conciliatory policies by hawks and doves.…”
Section: The Theoretical Basis Of the Hawk's Advantagementioning
confidence: 99%
See 2 more Smart Citations
“…Studies such as Sigelman and Sigelman (), Cuckierman and Tommasi (), and Cowen and Sutter () assume that the “election” or “poll” happens before the response by the other state is known and thus before the policy can be deemed successful or not. More recent work (e.g., Clare ; Colaresi ; Davies and Johns ; Schultz ) takes into consideration that voters might update their opinions based on the adversary's reaction. Interestingly, these studies formulate quite different expectations about how voters respond to success and failure of conciliatory policies by hawks and doves.…”
Section: The Theoretical Basis Of the Hawk's Advantagementioning
confidence: 99%
“…By contrast, Clare () argues that voters would reward, not penalize, a dove for successful rapprochement. At the same time, unsuccessful efforts by a hawk should be punished since they suggest foreign policy failure.…”
Section: The Theoretical Basis Of the Hawk's Advantagementioning
confidence: 99%
See 1 more Smart Citation
“…More recently, however, research on foreign policy has suggested that foreign and security policy is indeed an important area of disagreement among political parties (see, e.g., Bjereld and Demker, 2000;Özkeçeci-Taner, 2005;Schuster and Maier, 2006;Devine, 2009;Kaarbo, 2012;Calossi et al, 2013;Clare, 2014;Verbeek and Zaslove, 2015;Pijovic, 2016;Chryssogelos, 2018;Hofmann, 2017). Because foreign policy, including military missions, can be salient to voters and influence voting behaviour (cf.…”
Section: Party-political Contestation Of Military Missionsmentioning
confidence: 99%
“…Therefore, political parties that promote the welfare state tend to oppose large armies, expensive military procurement as well as the actual use of armed force abroad. Studies on the actual use of force find support for a left/right cleavage as 'right governments are more likely to be involved in militarized disputes than are left governments' (Palmer et al, 2004: 13; see also Rathbun, 2004;Arena and Palmer, 2009;Clare, 2010Clare, , 2014Oktay, 2014;Williams, 2014). Changing values in society, globalization, migration and the emergence of supranational authority have led students of party politics to consider additional cleavages that pit winners of globalization against losers (Kriesi et al, 2008) and/or proponents of post-materialist and cosmopolitan values against traditionalists and communitarians (Zürn and de Wilde, 2016;Hooghe and Marks, 2018).…”
Section: Party-political Contestation Of Military Missionsmentioning
confidence: 99%